Comportamento sísmico de um Pavilhão Pré-fabricado de Betão Armado - Nádia Batalha (2019)
Since precast concrete buildings are a constant in the industrial park in Portugal, and having shown poor performance in recent earthquakes both at structural and non-structural levels, their characterization becomes important in order to know better its seismic behavior. The one-story industrial buildings, with a frame structure of beams and columns, with a fixed connection at the base and hinged at the top, on which variable section beams are later supported is the most recurrent solution in Portugal. In this sense, this work deals with the seismic behavior of a frame of an existing industrial building, with prefabricated concrete structure. This characterization is performed through non-linear static analysis (pushover) and dynamic analysis. The results are presented and discussed.